British literature in transition, 1960-1980 : flower power - McLoughlin, Catherine Mary, 1970- (Cambridge : Cambridge University Press, 2019)
This volume traces transitions in British literature brought about by the rapid, momentous and far-reaching changes of the 1960s and 1970s, illuminating a diverse range of authors, texts, genres and movements. It looks at innovations in form, considering experimental poetry, fiction and drama, and explores the literature of emergent identities in race, gender, sexuality and class. It considers changes in attitudes and in the mind itself: the growth of environmentalism, perceptions of the past, psychedelia, the sexual revolution, and information control. It examines local and regional developments, visiting Wales, Scotland, Northern Ireland and northern England. Finally, it focuses on shifts within the oeuvres of individual authors - two poets, two dramatists and a novelist: Philip Larkin and Ted Hughes, Harold Pinter and Caryl Churchill, and Iris Murdoch.
Title from publisher's bibliographic system (viewed on 04 Jan 2019).
Keywords: English literature -- 20th century -- History and criticism